BIOLOGICAL CONTROL WITH CHESTNUT GALL WASP (Dryocosmus kuriphilus YASUMATSU) IN ZONGULDAK REGIONAL FOREST DIRECTORATE - Yıldız, Yafes; Albas, Ertan; Değirmenci, Bekir; Öföfoğlu, Gökberk; Yıldız, Yafes (Bartın Üniversitesi, 2025)
According to ancient Greek and Roman writers, chestnut, which was reported to have been taken from Anatolia to Greece in the 5th century BC and from there to Southern Italy and Spain, is an important species in the Fagaceae family, with both valuable fruit and wood. The species known as the European chestnut, which naturally spreads in forest areas in our country, is Castanea sativa. Chestnut grows at different altitudes from 200 m to 1800 m in its natural distribution area, depending on climate and latitude, and in regions where annual rainfall varies between 750 and 1200 mm and annual average temperature is between 8 C° and 15 ° C. The chestnut plant, which creates an important habitat for the ecosystem and acts as a food source for other living things, is under the threat of many diseases and pests, including its roots, trunks, branches, leaves and fruits. The chestnut gall wasp is a very important pest that prevents shoot development and flowering by laying its eggs in the buds of the chestnut and creating galls, causing 50-70% yield losses in the fruit, and causing damages that can lead to death in trees if population densities increase. The release of T. sinensis has been proven to be the most effective method for controlling the chestnut gall wasp. In this study, T. sinensis release studies carried out by the Zonguldak Regional Directorate of Forestry within the scope of chestnut gall wasp control between 2021-2025 were evaluated. The production of T. sinensis was carried out in the Forest Pests and Biological Control Laboratory in Gökçebey Forest Nursery. In order to preserve the parasitoids produced for release, processed boxes were kept in the cold at +6 °C. Since April, field exits were carried out to observe the galls formation in chestnut trees. According to the observations obtained from the field studies carried out during the period when the temperature values were 14-15 °C, in order to ensure the adaptation of T. sinensis to the external environment conditions, 2 °C increases were made per 2 days to equal to the external temperature. After the air temperature in the cold room was equalized with the external temperature, the galls in the boxes was taken to the production pergola in the open air. 334,185 galls were collected by the Zongıuldak Regional Directorate of Forestry for 5 years. 23,680 female and 13,302 male individuals obtained from these galls were released into nature. In the first 3 years of biological control studies, galls of Yalova origin and individuals obtained from these galls were used, while in 2024 and 2025, galls were collected mainly from within the borders of the Zonguldak Regional Directorate of Forestry and individuals obtained from these galls were used. In 2024 and 2025, the locations where gall collection activities were carried out were increased, and in this context; galls were collected from Ereğli (60), Cuma (96), Ormanlı (144), Gölderesi (99), Bendere (27), Kumluca (19), Kurucaşile (29), Amasra (87), Akçasu (66), Alaplı (38) and Kocaman (36) compartments. At the end of the 5-year biological control process, it was observed that only 10,000 of the 76,000 galls collected from Yalova Province, which was the leading location at the beginning of the process, were collected as of 2025, and Zonguldak Regional Directorate of Forestry’s resources were used at a rate of 86.84% in the supply of galls.

Eski Yunan ve Romalı yazarlara göre, M.Ö. 5. yüzyılda Anadolu’dan Yunanistan’a, buradan da Güney İtalya ve İspanya’ya götürüldüğü bildirilen kestane; Fagaceae (Kayıngiller) familyası içinde yer alan, hem meyvesi hem de odunu değerli olan önemli bir türdür. Ekosistem için önemli bir yaşam alanı oluşturan ve diğer canlılar için yiyecek kaynağı rolünü üstlenen kestane bitkisinin; kök, gövde, dal ve yaprakları ile meyveleri birçok hastalık ve zararlıların tehdidi altında bulunmaktadır. Kestane gal arısı yumurtalarını kestanenin tomurcuklarına bırakarak oluşturduğu galler ile sürgün gelişimi ve çiçeklenmeyi engelleyen, meyvede %50-70 arasında verim kayıplarına sebep olan, popülasyon yoğunluklarının artması durumunda ise ağaçlarda ölüme kadar varabilen zararlara yol açan çok önemli bir zararlıdır. T. sinensis salımının, kestane gal arısını kontrol etmek için en etkili yöntem olduğu kanıtlanmıştır. Bu çalışmada 2021-2025 yılları arasında kestane gal arısı ile mücadele kapsamında Zonguldak Orman Bölge Müdürlüğü tarafından gerçekleştirilen T.sinensis salımı çalışmaları değerlendirilmiştir. Zonguldak Orman Bölge Müdürlüğü tarafından 5 yıl boyunca 334.185 adet gal toplanmıştır. Bu galllerden elde edilen 23.680 dişi, 13302 erkek bireyin doğaya salımı gerçekleştirilmiştir. Biyolojik mücadele çalışmalarının ilk 3 yıllık periyodunda, ağırlıklı olarak Yalova orijinli galler ve bu gallerden elde edilen bireyler kullanılırken, 2024 ve 2025 yıllarında ağırlıklı olarak Zonguldak Orman Bölge Müdürlüğü sınırları içerisinden galler toplanmış ve bu gallerden elde edilen bireyler kullanılmıştır.
ZONGULDAK ORMAN BÖLGE MÜDÜRLÜĞÜNDE KESTANE GAL ARISI (Dryocosmus kuriphilus YASUMATSU) İLE BİYOLOJİK MÜCADELE ÇALIŞMALARI
Keywords: Ecology (Other); Ekoloji (Diğer)